Dermoscopy of Gottron's papules and other inflammatory dermatoses involving the dorsa of the hands. (19th March 2022) - Żychowska, M.; Łudzik, J.; Witkowski, A.; Lee, C.; Reich, A.
Abstract: Background: Several inflammatory dermatoses, including dermatomyositis (DM), may present as erythematous papules or plaques on the dorsal aspects of the hands over the joints. Limited skin involvement in these entities may pose a diagnostic challenge. (Video)dermoscopy is being utilized more frequently to aid in the differential diagnosis of inflammatory skin conditions. Objective: To describe the dermoscopic findings in Gottron's papules and compare them with dermoscopic features of other dermatoses involving the dorsal aspects of the hands. Methods: Videodermoscopic images from patients presenting with erythematous papules or plaques on the dorsal surface of the hands were retrospectively analysed for the presence of standardized dermoscopic parameters. Results: Dermoscopic images from patients with DM ( n  = 12), psoriasis ( n  = 19), chronic dermatitis ( n  = 16), mycosis fungoides ( n  = 7), lichen planus ( n  = 5) and pityriasis rubra pilaris ( n  = 3) were included. Gottron's papules were characterized by pleomorphic vessels (dotted vessels accompanied by thick or thin linear vessels with branches or linear curved vessels) in 66.7% of cases, arranged in an unspecified pattern (91.7%), and accompanied by white or pink structureless areas (75.0%). Psoriatic plaques were characterized by dotted vessels arranged in a uniform pattern (94.7%). Vessels arranged in a ring pattern were nearly exclusively observed in psoriasis, while yellow structureless areas and erosions were more frequently present in chronic dermatitis. White lines, corresponding to Wickham striae, were specific for lichen planus. Conclusions: Videodermoscopy might be of value in differentiating Gottron's papules from other dermatoses involving dorsa of the hands.